2018
DOI: 10.1002/jnr.24250
|View full text |Cite
|
Sign up to set email alerts
|

Insights into optic pathway glioma vision loss from mouse models of neurofibromatosis type 1

Abstract: Neurofibromatosis type 1 (NF1) is a common cancer predisposition syndrome caused by mutations in the NF1 gene. The NF1-encoded protein (neurofibromin) is an inhibitor of the oncoprotein RAS and controls cell growth and survival. Individuals with NF1 are prone to developing low-grade tumors of the optic nerves, chiasm, tracts, and radiations, termed optic pathway gliomas (OPGs), which can cause vision loss. A paucity of surgical tumor specimens and of patient-derived xenografts for investigative studies has lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…The most frequent central nervous system (CNS) tumors observed in NF1 are gliomas which concern about 20% of patients [65]. They are mainly low-grade gliomas of the optic pathways and are most often classified as pilocytic astrocytoma [66][67][68]. In our cohort, OPGs were present in 11% (9/80) of patients and were responsible for loss of visual acuity in three patients, with one presenting bilateral optic atrophy.…”
Section: Discussionmentioning
confidence: 80%
“…The most frequent central nervous system (CNS) tumors observed in NF1 are gliomas which concern about 20% of patients [65]. They are mainly low-grade gliomas of the optic pathways and are most often classified as pilocytic astrocytoma [66][67][68]. In our cohort, OPGs were present in 11% (9/80) of patients and were responsible for loss of visual acuity in three patients, with one presenting bilateral optic atrophy.…”
Section: Discussionmentioning
confidence: 80%
“…They can be utilized as specific biomarkers for guiding the screening, diagnosis and treatment, and predicting the prognosis of glioma (12). The development of targeted therapy based on these biomarkers is a promising approach to improving glioma patients' poor prognosis (13,14). identified that SIPA1 is located on the metastasis efficiency modifier locus mtes1.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenetic mechanisms at the basis of OPG development in NF1 are not completely understood, thus reducing the possibility to develop effective treatments. The main limitations for the study of the molecular pathways leading to OPG have been the paucity of biological samples, given the low rate of surgery, and the difficulty to obtain patient-derived xenograft-models or cell lines from these tumors [85]. However, over the last few years distinct strategies have been used to investigate gliomagenesis.…”
Section: Preclinical Models Of Opgmentioning
confidence: 99%
“…Furthermore, these engineered models of NF1 were crucial to confirming the role of RAS hyperactivation in the development of OPG, providing the biological rationale to test a series of compounds able to counteract the effectors downstream to RAS: the RAS-MEK-ERK and the PI3K-AKT-mTOR signaling pathways are up-regulated in tumor cells [91,92,93], whereas the adenylyl cyclase-mediated cyclic AMP is associated with decreased levels of cAMP [94]. However, some of the drugs acting on these pathways (including the mTOR inhibitor Rapamycin) are active in mice only during therapy, with recovery of tumor growth after treatment suspension [85].…”
Section: Preclinical Models Of Opgmentioning
confidence: 99%